Peningkatan Mutu SDM Melalui Pendidikan Dan Pemberdayaan Di Desa Belitar Seberang Kabupaten Rejang Lebong - Mariska Febrianti; Ajis Sumantri; Dody Ertanto; Ahmad Yeri; Yoza Muklas (Jurnal Dehasen Untuk Negeri, 2023)
The development of tourism in rural areas using the community participation method is an ideal condition that can be achieved on the basis of community enthusiasm as the basic and main capital. It is supported by the availability of natural and cultural resources, good governance, and also academics or other institutions as facilitators. In terms of developing tourism in Belitar Seberang Village, the Physical Education Study Program has a supporting role through community service activities in the development of a tourist village because this village is Dehasen University Bengkulu Development Village. It is intended so that there is an integration between the activities carried out. Then, assistance activities will be carried out in Mei 2023. This activity will contribute to the development of tourist attractions, especially nature tourism, and tourist accommodation in the form of homestays. Using the potential of institutional networks, the Physical Education Study Program collaborates with students and lecturers to jointly transfer knowledge to the community as owners and managers of tourist destinations. Interaction is carried out with the community through direct discussions in forum, namely tourism awareness groups (Pokdarwis). The results of the activity show that mentoring the development of tourism villages in a sustainable manner is able to build community enthusiasm to continue participate in village tourism development activities.